Korelasi Kemampuan Membaca Al-Qur’an terhadap Hasil Belajar Siswa Kelas X SMK Plus Umar Zahid pada Mata Pelajaran Sains - M. Qoyum Zuhriawan; M. Aliyul Wafa; Dian Khanifah (PT. Hasba Edukasi Mandiri, 2025)
This study aims to determine the relationship between the ability to read the Qur'an with the learning outcomes of Science subjects in class X students of SMK Plus Umar Zahid. The ability to read the Qur'an is seen as an important indicator in character building and spiritual intelligence of students, which has the potential to affect academic achievement, especially in science. This study used a correlational quantitative approach, with data collection techniques through a test of Al-Qur'an reading ability as well as documentation of Science subject scores. The sample amounted to 75 students selected by random sampling from all grade X students. Data analysis was carried out through normality, linearity, and simple regression tests using SPSS software version 26. The results of the analysis showed a positive and significant correlation between the ability to read the Qur'an and Science learning outcomes. That is, the better students' ability to read the Qur'an, the higher their learning outcomes in Science subjects. This finding strengthens the assumption that religious literacy, especially in reading and understanding the Qur'an can contribute to supporting the mastery of general science. Thus, the integration between religious education and general education can be an effective strategy in shaping learners who not only excel academically, but also have a strong moral and spiritual foundation.